Reconstruction of Radiation Dose Received by Diagnostic Radiologic Technologists in Korea - Yeongchull Choi; Jaeyoung Kim; Jung Jeung Lee; Jae Kwan Jun; Won Jin Lee (Korean Society for Preventive Medicine, 2016)
Objectives Diagnostic medical radiation workers in Korea have been officially monitored for their occupational radiation doses since 1996. The purpose of this study was to design models for reconstructing unknown individual radiation doses to which diagnostic radiation technologists were exposed before 1996. Methods Radiation dose reconstruction models were developed by using cross-sectional survey data and the personal badge doses of 8167 radiologic technologists. The models included calendar year and age as predictors, and the participants were grouped into six categories according to their sex and facility type. The annual doses between 1971 and 1995 for those who were employed before 1996 were estimated using these models. Results The calendar year and age were inversely related to the estimated radiation doses in the models of all six groups. The annual median estimated doses decreased from 9.45 mSv in 1971 to 1.26 mSv in 1995, and the associated dose variation also decreased with time. The estimated median badge doses from 1996 (1.22 mSv) to 2011 (0.30 mSv) were similar to the measured doses (1.68 mSv to 0.21 mSv) for the same years. Similar results were observed for all six groups. Conclusions The reconstruction models developed in this study may be useful for estimating historical occupational radiation doses received by medical radiologic technologists in Korea.